2006
DOI: 10.1523/jneurosci.5495-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Transient and Sustained Response Components of V4 Neurons by Temporal Crowding in Flashed Stimulus Sequences

Abstract: The responses of extrastriate area V4 neurons to flashed visual stimuli were examined to determine whether the responses to stimulus sequences occurring at normal saccade and fixation timing intervals were degraded relative to longer timing intervals. Stimuli were flashed in receptive fields in the near periphery while monkeys maintained steady fixation. Short interstimulus intervals (ISIs) resulted in an overall habituation style response reduction. The transient component of responses to preferred stimuli wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
67
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 31 publications
8
67
1
Order By: Relevance
“…Introduction again similar to aMMN that can be elicited by rare changes in more abstract attributes of the acoustic stimuli than simple physical features, vMMN is also sensitive to higher-level attributes such as sequential regularities (Stefanics, Kimura, et al, 2011), object structure (Mü ller, Widmann, & Schr€ oger, 2013), symmetry (Kecskes-Kovacs, Sulykos, & Czigler, 2013a), laterality of body parts , or attributes of socially more relevant stimuli such as facial emotions (Astikainen & Hietanen, 2009;Fujimura & Okanoya, 2013;Susac, Ilmoniemi, Pihko, Ranken, & Supek, 2010;Susac, Ilmoniemi, Pihko, & Supek, 2004;Zhao & Li, 2006), as well as facial gender (Kecskes-Kovacs, Sulykos, & Czigler, 2013b). Thus, there is ample evidence that automatic perceptual predictive mechanisms operate in the visual modality too, which can be probed by experimentally manipulating statistical properties of a wide variety of stimulus attributes or their relationships.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Introduction again similar to aMMN that can be elicited by rare changes in more abstract attributes of the acoustic stimuli than simple physical features, vMMN is also sensitive to higher-level attributes such as sequential regularities (Stefanics, Kimura, et al, 2011), object structure (Mü ller, Widmann, & Schr€ oger, 2013), symmetry (Kecskes-Kovacs, Sulykos, & Czigler, 2013a), laterality of body parts , or attributes of socially more relevant stimuli such as facial emotions (Astikainen & Hietanen, 2009;Fujimura & Okanoya, 2013;Susac, Ilmoniemi, Pihko, Ranken, & Supek, 2010;Susac, Ilmoniemi, Pihko, & Supek, 2004;Zhao & Li, 2006), as well as facial gender (Kecskes-Kovacs, Sulykos, & Czigler, 2013b). Thus, there is ample evidence that automatic perceptual predictive mechanisms operate in the visual modality too, which can be probed by experimentally manipulating statistical properties of a wide variety of stimulus attributes or their relationships.…”
mentioning
confidence: 99%
“…This is in line with a recent EEG study where SSA was found to depend critically on statistical context in the auditory cortex (Herrmann, Henry, Fromboluti, McAuley, & Obleser, 2015), and that aMMN itself is a compound response of primary and higher-level cortical areas with longer response latencies. Adaptation has been observed in electrophysiological studies throughout the visual system including the retina (Hosoya, Baccus, & Meister, 2005), thalamus (Solomon, Peirce, Dhruv, & Lennie, 2004), superior colliculus (Boehnke et al, 2011), and several cortical areas (Kaliukhovich & Vogels, 2014;Kremlacek et al, 2007;Meyer, Ramachandran, & Olson, 2014;Motter, 2006;Mü ller, Metha, Krauskopf, & Lennie, 1999;Ramachandran, Meyer, & Olson, 2016; for a review, see Vogels, in press). Although the exact relationship of adaptation at different levels of the visual processing hierarchy to change detection as observed in vMMN studies (e.g., Kimura et al, 2011;Stefanics et al, 2014) is not clear, there is general agreement that the function of adaptation is to match response properties of the sensory system to the current environment (Clifford et al, 2007;Webster, 2011) and thus improve stimulus discrimination or detection of improbable stimuli (Benucci, Saleem & Carandini, 2013;Carandini & Heeger, 2012;Kohn, 2007;Solomon & Kohn, 2014;Wark, Lundstrom, & Fairhall, 2007).…”
mentioning
confidence: 99%
“…This paucity of research is surprising given the wealth of data collected in the psychophysical literature regarding the temporal phenomena of visual masking and inhibition of return. A recent paper in the Journal of Neuroscience (Motter, 2006) begins to fill this conceptual void. The author recorded from visual area V4 in awake behaving monkeys while long sequences of stimuli were presented.…”
mentioning
confidence: 99%
“…Monkeys fixated a spot while six to eight letter-like stimuli were flashed in the receptive field [Motter (2006), his Fig. 1 (http://www.…”
mentioning
confidence: 99%
See 1 more Smart Citation